Responsibility for crimes against the world and safety of mankind (Journal of actual problems of jurisprudence, 2019)
In article the role of the Nuremberg process about establishment of responsibility for these types of serious crimes isshined questions of criminal liability for crimes against the world and mankind.Key words: nazi set, fascist doctrine, Geneva convention.